DISSOLVED AND PARTICULATE CARBON IN JAKARTA BAY, INDONESIA - Nugrahadi, Mochamad Saleh; Yanagi, Tetsuo; Tejakusuma, I. G.; Adi, Seno; Darmawan, Rahmania A. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2009)
In order to investigate spatial and temporal variability of dissolved organic carbon (DOC) and particulate organic carbon (POC), several samples were collected from five estuaries, inner part and outer part of Jakarta Bay. The samples were collected on 15 and 16 February 2007, a week after heavy flood in Jakarta Area, and on 16 May 2007. DOC concentration in February and May in Jakarta Bay ranged between 100-950 µg-C/l and between 0-850 µg-C/l respectively. POC concentrations ranged between 50-650 µg-C /l and 50-900 µg-C /1 in February and May 2007, respectively. Even though the concentrations between both periods were similar, the load of organic carbon from the land to Jakarta Bay showed a large contrast due to the different amount of freshwater input. The Total organic carbon fluxes from the rivers to the bay in February and May 2007 were 107.6 t d-' C-(ton per day Carbon) and 42.7 t d-1 C, respectively.